Real-world efficacy and safety of cefepime for pediatric community-acquired pneumonia: a propensity score-matched study - Liu, Changxin; Deng, Jiayu; Xing, Yudi; Song, Yanqing (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to evaluate the real-world clinical efficacy and safety of cefepime in treating pediatric community-acquired pneumonia (CAP), comparing it with other broad-spectrum antibiotics, including cefoperazone-sulbactam and meropenem, using a propensity score-matched design.MethodsA retrospective, propensity score-matched cohort study was conducted in pediatric patients (0–18 years) hospitalized with CAP. Patients treated with cefepime were compared to those treated with cefoperazone-sulbactam or meropenem. Clinical outcomes, microbiological clearance, and adverse events were assessed, and propensity score matching was applied to minimize confounding.ResultsA total of 788 patients were included, with 720 in the cefepime group and 68 in the comparator group. Both groups showed comparable clinical efficacy, with no significant differences in symptom resolution, laboratory normalization, or radiographic improvement. Microbiological clearance rates were also similar between the groups. The incidence of adverse events was low in both groups, and no statistically significant difference in adverse events was observed between cefepime and the comparator group.ConclusionOur results suggest that cefepime is a clinically effective and well-tolerated alternative to other broad-spectrum antibiotics for pediatric CAP, demonstrating comparable clinical outcomes and safety profiles. These findings support cefepime as a viable empiric therapy option, particularly in settings with limited microbiological diagnostics. Further studies are needed to confirm these results and optimize dosing strategies for pediatric populations.